GAMBARAN PENGETAHUAN PASIEN DIABETES MELLITUS TENTANG PERAWATAN LUKA ULKUS DIABETIK DI KLINIK IKHZA MEDIKA: DESCRIPTION OF DIABETES MELITUS PATIENTS REGARDING DIABETIC ULCER TREATMENT IN IKHZA MEDICAL CLINIC - Anam, Agus Khoirul; Kurniawan, Bayu Puguh Dwi (Bali Medika Jurnal, 2019)
Diabetic ulcers are a chronic form of diabetes mellitus in the form of open sores on the skin surface that can be accompanied by local tissue death. Thus, patients need to know about the treatment of diabeteic ulcer wounds to speed up the wound healing process. The purpose of this study is to describe the knowledge of patients with diabetes mellitus about the treatment of diabetic ulcer wounds. This research method uses descriptive design. The population in this study were diabetic mellitus patients who underwent wound care at Ikhza Medika Clinic as many as 31 people and the sample size was total population. Data collection was carried out using a questionnaire. When the data was collected on April 8 to May 22, 2017. The results of the study showed that the knowledge of patients about the treatment of diabetic ulcer injuries was categorized as sufficient with a percentage of 51.6% as many as 16 people. Recommendations for the Ikhza Medika Clinic are expected to be used as input in an effort to increase the knowledge of patients with diabetes mellitus about the treatment of diabetic ulcer wounds by providing counseling or education to diabetic ulcer patients during wound care.